The principle of fairness in standard agreements in the financial services sector for consumer legal protection - Reja Haryadi; Martin Roestamy; Sudiman Sihotang (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aims to examine and analyze the application of the principle of fairness in standard agreements within the financial services sector concerning consumer legal protection, as regulated under Law No. 8 of 1999 on Consumer Protection. The research adopts a normative juridical approach, collecting and analyzing data through literature studies and statutory approaches, supplemented by case studies to assess real-world applications. The findings reveal that standard agreements in financial services, which are predominantly unilaterally drafted by financial service providers (PUJK), often result in unfair conditions for consumers. These agreements lack a bargaining process, effectively leaving consumers in a weak position where they can only choose to either accept or reject the agreement in its entirety (take it or leave it). The novelty of this research lies in its detailed examination of power imbalances in financial agreements, demonstrating that consumer vulnerability stems from their dependency on financial services, which limits their negotiating power. Unlike previous studies, this research not only highlights these imbalances but also proposes regulatory improvements, such as mandatory fairness reviews and enhanced consumer rights protections, to address the injustices arising from unilateral contractual provisions. These findings are expected to contribute to policy recommendations that promote more equitable contractual relationships between financial service providers and consumers.